(3CYdGe GdfHhIs - (3Ydj Hf eMeO MHjH, CHh GdMSf GdeGhQOj,J (B450 (3g` s ((3YjSi Hf OGhO Hf YHOGdYdj GdSjaj s)
(3ChdgG (B:s
(3ddg GdCLQ ef Pdc eSJYjfkG Hg YR LGQg (B[ (3cPG , hdYdgG (B: (3LGgdI(B] (3Cf jdgefj GdUhGH hGdQTGO s
(3BNQgG (B:s
(3hgh CYde MjK jLYd QSGdJg hdGjTQc ai Mceg CMOG s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B327 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B189s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B39 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs